INDONESIAN LANGUAGE LEARNING AND MULTICULTURAL CITIZENSHIP: THE ROLE OF CHINESE-INDONESIAN STUDENTS IN SHAPING PANCASILA VALUES - Martono Martono; Iwan Ramadhan; Jagad Aditya Dewantara; Muhammad Agus Hardiansyah; Muhammad Iqbal; Nasrin Nabila (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
SMPN 7 and SMPN 19 in Singkawang have approximately 65% students of Chinese descent. Persistent stereotypes often marginalize the role of the Chinese community by reducing it solely to economic dominance, leading to the assumption that their involvement is merely profit-oriented. The implementation of the Pancasila Student Profile (P5) supports the active participation of Chinese-Indonesian students in collectively shaping Pancasila values. In this context, Chinese-Indonesian students serve as key agents in fostering the development of an inclusive national character. This study aims to describe how Indonesian language learning can be implemented to strengthen the values of the Pancasila Student Profile in a multicultural school environment, specifically at SMPN 7 and SMPN 19 Singkawang. Using a qualitative descriptive approach, data were collected through observations, interviews with school principals, Indonesian language teachers, and students, and documentation of school activities. Indonesian language learning at SMPN 7 and SMPN 19 Singkawang has been proven to play a strategic role in strengthening the values of the Pancasila Student Profile through the development of character, tolerance, and nationalism within a multicultural school environment, while simultaneously affirming the active role of Chinese-Indonesian students as agents in shaping an inclusive national identity. At SMPN 7 Singkawang, interfaith celebrations such as Eid, Chinese New Year, and Christmas serve as inclusive spaces for interaction that foster mutual respect. Meanwhile, SMPN 19 regularly organizes cultural art weeks that showcase ethnic diversity to reinforce a pluralistic national identity. Chinese-Indonesian students are not merely recipients but also active agents in building an inclusive and tolerant national identity.